O uso analítico do sonho: um recorte da contribuição winnicottiana - Cocco, Maria Regina (2017)
The presente research aimed to design a clipping of the Winnicottian contribution to the analytical use of the dream, along the initial stages of emotional development prior to the repressed unconscious. As specific objectives, it was studied: a) the dream as an experience of integration, constitution and communication of the individual with himself and with the other; b) the provision of this experience within the context of the analytical setting; and c) the analytical use of the dream inscribed in the process of maturation. In the methodology, it was used: 1) the bibliographical research to: a) contextualize the Winnicottian contribution on the analytical use of the dream in the psychoanalytic literature; b) revisit the Winnicottian theoretical foundation; and c) to select Winnicottian texts whose clinical accounts illustrate the use of the dream and allow a recognition of subsidies to the analytical clinic; 2) research-listening and research-investigative in the clinical fragments of a psychoanalytic case, with which reflected on the analytical use of the dream with the borderline patient. The project was based on the Winnicottian theoretical / clinical conception to support the proposal that, in the initial phases of maturation process, the dream and the experiences of to play have their roots in the imaginative elaboration of body functioning and are fundamentally in the integration and in story of the self and, besides the cultural experiences, open a space of intertwining and enrichment of the human being's life